Large apical thrombus in a patient with persistent heart failure and hypereosinophilia: Loffler endocarditis - ÖZBEN SADIÇ, BESTE (SPRINGER, 2008)
Idiopathic hypereosinophilic syndrome is an uncommon leukoproliferative systemic disorder characterized by the overproduction of eosinophils and poor prognosis. A major source of morbidity and mortality of this syndrome is the associated cardiac involvement represented by endocardial thickening and mural thrombi. We report a 64-year-old woman with persistent symptoms of heart failure despite standard medical therapy. Echocardiography revealed reduced left ventricular filling due to a large apical mass; an abnormal diastolic filling pattern was also noticed. Complete blood count revealed remarkable hypereosinophilia. Cardiac magnetic resonance imaging demonstrated an apical thrombus and intense linear enhancement of the endocardium, which were compatible with Loffler endocarditis. Medical therapy, including corticosteroids and anticoagulation, was initiated promptly. The symptoms improved as the peripheral hypereosinophilia resolved in 15 days. The patient was asymptomatic at the 1-year follow-up visit with complete regression of the apical thrombus and no evidence of restrictive cardiomyopathy. We report this case to draw attention to this particularly rare condition with poor prognosis since quick and accurate diagnosis and prompt initiation of therapy may improve symptoms and survival.
Keywords: cardiac thrombus; endocarditis; heart failure; Loffler endocarditis; ENDOMYOCARDIAL FIBROSIS; RESTRICTIVE CARDIOMYOPATHY; ECHOCARDIOGRAPHIC FEATURES; FOLLOW-UP; EOSINOPHILIA; INVOLVEMENT; MANAGEMENT; DIAGNOSIS; SURGERY; FUSION